A Study Of Acoustic Emission Intensity Effect During Fuel Injector Fault - Z. M., Hafizi; C. K. E., Nizwan; D. M., Firdaus (Universiti Malaysia Pahang, 2010)

(untitled)
Engine condition monitoring is one of the preventive actions that keep the performance of an engine at the top range. One of the nondestructive testing; Acoustic Emission Technique, offers an effective ways to detect the engine fault without dissemble the engine. This paper presented a study of Acoustic Emission intensity produced by fuel injector fault during engine running under idle condition. The experimental work was carried out on a four cylinder petrol engine. An Acoustic Emission device; AED-2000V Virtual Instrument was used to acquire the emitted signals. All data was recorded and analyzed to see the ratio between good and fault fuel injector condition. It can be concluded that the ratio was in the range of 0.1 to 0.2 and significant as an early indicator of fuel injector malfunction.